PELUANG DAN TANTANGAN MANAJEMEN SUMBER DAYA DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN DI ERA SOCIETY 5.0 - Candra Candra; Zahara Zahara; Fauzan Hakim; Akhir Lusono; Kraugusteeliana Kraugusteeliana (ITB AAS Indonesia Surakarta, 2024)
The Society 5.0 era presents various opportunities and challenges for resource management in increasing employee productivity. The main opportunities presented include the use of advanced technology. And challenges arise where with sophisticated technology, data security is the main thing. This research aims to look at the opportunities and challenges in increasing employee productivity in the era of society 5.0 . This research method uses library research, with the main source of this research coming from journals, articles or related books. The results of this research are opportunities, namely increasingly sophisticated technology, work flexibility, training and development as well as employee welfare and health. Furthermore, challenges include data security and privacy, technology adaptation, managing remote work, regulations and policies. To overcome all this, continuous training, flexible policies and support for mental well-being as well as investment in cyber security are expected.